2018
DOI: 10.1016/j.clbc.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Affecting Breast Cancer-related Lymphedema: Serial Body Weight Change During Neoadjuvant Anthracycline Plus Cyclophosphamide Followed by Taxane

Abstract: Because a BMI ≥ 25 kg/m was an independent factor of LE occurrence on multivariate analysis, patients with a preoperative BMI ≥ 25 kg/m should be closely monitored for LE given their increased risk, and monitoring and education should be initiated before surgery and continued throughout the course of NAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…There were no significant differences between the two groups in any demographic (age, BMI, and weight) or breast cancer-related characteristics (affected site, pathological stage group, recurrence, surgery method, number of dissected lymph nodes, time since first breast cancer surgery, and administration of radiotherapy and chemotherapy). Patients who received radiotherapy and chemotherapy were administrated with radiotherapy according to their clinical stage followed by neoadjuvant systemic chemotherapy (NAC) [29].…”
Section: Resultsmentioning
confidence: 99%
“…There were no significant differences between the two groups in any demographic (age, BMI, and weight) or breast cancer-related characteristics (affected site, pathological stage group, recurrence, surgery method, number of dissected lymph nodes, time since first breast cancer surgery, and administration of radiotherapy and chemotherapy). Patients who received radiotherapy and chemotherapy were administrated with radiotherapy according to their clinical stage followed by neoadjuvant systemic chemotherapy (NAC) [29].…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 shows the results of a multivariable regression model includ- Numerous studies have identified elevated BMI as an important risk factor in this context (Can et al, 2016;DiSipio et al, 2013;Duyur Caklt et al, 2019;Leray et al, 2020;Park et al, 2018;Rastogi et al, 2018;Tsai et al, 2020;Winkels et al, 2017), and it has been specifically associated with increased swelling of the affected arm (Rastogi et al, 2018) and an almost twofold higher risk of BCRL (Chooi et al, 2019). In the study by Park et al, (2018), BMI ≥ 25 kg/m 2 was an independent risk factor for lymphoedema in an analysis of 406 women who received neoadjuvant chemotherapy prior to surgery. In relation to the management of BCRL, Tsai et al, (2020), in a systematic review of 461 studies, concluded that weight reduction significantly reduced the volume of the affected and unaffected arms.…”
Section: Prediction Model For the Risk Of Lymphoedemamentioning
confidence: 99%
“…1 The average incidence of secondary lymphedema in women following breast cancer treatment is 20%, 2,3 and with a number of studies reporting an increased incidence of up to 60%. [4][5][6] These numbers indicate that lymphedema is one of the most pressing survivorship issues among women who have been treated for breast cancer, though sustainable treatment options remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphedema is a common complication in cancer survivors with an overall incidence of 15.5%, and increased risk among patients who undergo pelvic dissections (22%) or radiation therapy (31%) 1 . The average incidence of secondary lymphedema in women following breast cancer treatment is 20%, 2,3 and with a number of studies reporting an increased incidence of up to 60% 4–6 . These numbers indicate that lymphedema is one of the most pressing survivorship issues among women who have been treated for breast cancer, though sustainable treatment options remain elusive.…”
Section: Introductionmentioning
confidence: 99%